REAL ESTATE MARKET DYNAMICS IN UZBEKISTAN: ASSESSING FACTORS INFLUENCING THE REAL ESTATE MARKET INCLUDING URBAN DEVELOPMENT POLICIES, INVESTMENT TRENDS, AND ECONOMIC GROWTH - Shoh-Jаkhon Khаmdаmov; Amirbek Azizbekovich Akhrorov (International Journal of Artificial Intelligence for Digital Marketing, 2024)
This thesis describes, what is the real estate market, its operating principles, structures, population demand for real estate, offers and prices made by suppliers, laws of supply and demand in the market, how does it work in Uzbekistan’s market, real estate in Uzbekistan and around the world and also, about the changes of demand over the years, the current situation, professions working in this field and their duties. In this thesis you can learn how to choose the right field for investing, what kind of key-factors can influence to the real estate market in Uzbekistan comparing to the most-developed countries market system, examples, digitalization, developing online platforms and programs which works with real estate market and etc. Additionally, it provides a comprehensive examination of the real estate landscape in Uzbekistan, offering insights into its unique characteristics, regulatory framework, and future prospects. Through comparative analysis, this study aims to shed light on the similarities, differences, and potential synergies between global real estate dynamics and those observed within Uzbekistan